The impact of partner performance on emotions in doubles racquet sports - Deck, S.; Hall, C.; Wilson, P. M. (Research Quarterly for Exercise and Sport, 2021)
Purpose: Different athletes may experience different emotions, based on one`s appraisal of the situation or environment. To date, this line of research has received limited research attention in sport dyads. The purpose of this study was to understand the role of a partner`s play on the different types of emotion of athletes, as well as perceived impact on overall emotions, performance, and motivation in doubles racquet sports (i.e., tennis, badminton, and squash). Method: Using a post-test only, randomized experimental design, participants read one of three possible written vignettes that depicted different scenarios of their partner`s play (i.e., poor, good, or usual performance). Participants (N = 103) were then asked to fill out a questionnaire packet based on the scenario read. Results: A Multivariate Analysis of Variance, as well as follow-up Analyses of Variance revealed significant differences between groups in subjective emotions based on whether their partner was playing poorly, their partner having a good performance or whether their partner was perceived as playing their usual game (control group). The results showed that athletes scored higher in anger and anxiety when their partner is playing poorly, and when their partner is having a good performance, athletes had higher scores in happiness and excitement. Conclusion: Overall, these findings imply that athletes` emotions may change based on how their partner is playing and provide a foundation to look at emotional reactions (action tendencies) and coping in sport teams.